De Voogd, Peter, and John Neubauer, eds. The Reception of Laurence Sterne in Europe. London: Continuum, 2004. 332 pp. - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The ambitious series bearing the general title The Reception of British Authors in Europe (series editor: Elinor Shaffer) published in the Athlone Critical Traditions Series by Thoemmes Continuum made its début last year with a volume on the reception of Virginia Woolf. Second in the series, The Reception of Laurence Sterne in Europe traces how the writing of Sterne crossed the English Channel to affect national literatures from the Iberian Peninsula to Scandinavia, from the Netherlands to Russia. The authors of critical articles on national receptions provide guidance to this journey across the continent and reveal how, transcending national, cultural and political barriers, Sterne’s works changed generic conventions of the novel as well as conceptions of sensibility. The volume opens up new cultural vistas from the eighteenth century to the present in investigations related to the historical and theoretical aspects of the European novel, ensuring that the approaches should be as multifaceted as the whimsical eighteenth-century author himself.